Mucinous carcinoma of the breast: epidemiological, clinical, and prognostic characteristics; a single-center experience - Omar Hamdy; Mosab Shetiwy; Mahmoud M. Saber; Basma A. Eldawody; Shorouq A. Kassab; Mariam H. Nabih; Mostafa Abdelhakiem; Mona Zaki; Shaimaa M. Yussif; Saleh Saleh; Khaled Abdelwahab (Discover Oncology)
Abstract Introduction Mucinous (colloid) carcinoma (MC) of the breast typically affects postmenopausal and elderly women, with a more favorable prognosis compared to invasive breast carcinoma of no special type (IBC-NST). It is characterized by the presence of extracellular mucin and better outcomes. In our work, we presented a fifteen-year yield of a tertiary cancer center for MC. Methods In this retrospective study, the data of the patients with MC from January 2009 to August 2023 were retrieved by searching the prospectively registered electronic database of the Oncology Center, Mansoura University. The patients’ epidemiological, clinical, pathological, therapeutic, and oncological data were analyzed. Results A total of 152 patients with the pathology of MC of the breast were included. The mean age of patients was 55.38 ± 13.82 years. Imaging revealed a unifocal lesion in 93 patients (61.2%). The mean mass size by imaging was 37.25 ± 20.21 mm. Positive lymph nodes (LNs) were detected by imaging in 71 (46.7%) patients. Pathological variants were either pure MC (42.1%) or mixed mucinous ductal carcinoma (57.9%). Luminal A was the most common subtype. Neoadjuvant therapy (NAT) was received by 34.8% of the patients. Mastectomy was done for 103 patients (68.2%). Axillary lymph node dissection was done for 122 patients (80.3%), and sentinel lymph node biopsy (SLNB) was done for 30 patients (19.7%). Adjuvant chemotherapy and radiotherapy were received by 65.1% and 60.8% of patients, respectively, while adjuvant hormonal therapy was received by 84.5%. The mean disease-free survival (DFS) was 43 ± 34.02 months, while the mean overall survival (OAS) was 44.5 ± 33.46 months. Seventeen patients (11.2%) were reported dead during the follow-up period. Conclusion MC of the breast is a unique type of breast cancer. It may mimic benign lesions on imaging. The primary treatment for MC is mostly surgery, followed by adjuvant radiotherapy and systemic therapy. Comparing MC to IBC-NST, the former had a better prognosis and fewer lymphatic metastases, especially with pure MC, which shows a better prognosis.